2011
DOI: 10.3102/1076998610381397
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Critical Values for Strength of Alignment Among Curriculum, Assessments, and Instruction

Abstract: School accountability decisions based on standardized tests hinge on the degree of alignment of the test with the state's standards documents. Yet, there exist no established criteria for judging strength of alignment. Previous measures of alignment among tests, standards, and teachers' instruction have yielded mixed results that are difficult to interpret and to compare across studies. This article reports findings from a simulation study to determine critical values for Porter's alignment index, suitable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 14 publications
(40 reference statements)
1
34
0
1
Order By: Relevance
“…Making an appropriate comparand by parsing the contents of source documents is part of the alignment comparison. The choice of how to parse, and why, would affect the results of a comparison; the coarser grain at which one compares, the easier it may be to find agreement between a proposed curriculum and a set of standards (Fulmer, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Making an appropriate comparand by parsing the contents of source documents is part of the alignment comparison. The choice of how to parse, and why, would affect the results of a comparison; the coarser grain at which one compares, the easier it may be to find agreement between a proposed curriculum and a set of standards (Fulmer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Methodologically, the biggest challenge is how to produce a meaningful interpretation for integration, whether as a quantifiable score or a qualitative judgment. Quantitatively, Fulmer et al (2011, 2014) showed how Porter's index can be interpreted statistically, but this is inadequate for the three‐dimensional nature of NGSS. Further work is needed to try out alternative alignment scoring or indices, such as attending to multivariate distance, or weighting so that quality of integration could attenuate or amplify a score that was based only on coverage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important measure to understand the effectiveness of such content delivery and its assessment is the alignment of a curriculum with its objectives and assessment outcomes. Such studies have been carried out in United States [5][6][7] in Africa [8,9], in China [10][11][12] and in Singapore [13] and have assisted policy makers and curriculum and assessment developers to enhance their materials coherence and consistency. This paper seeks to explore such alignment in the physics curricula and examination materials in the two previously unresearched contexts of Myanmar and South Australia in comparison with previously carried out alignment studies (from New York, China and Singapore).…”
Section: Introductionmentioning
confidence: 99%